Expression of FasL in Proliferation of Retinoblastoma Cells: A Mechanism Fas Counterattack - Hendrian Dwikoloso Soebagjo; Hidayat Sujuti; Hasan Machfoed; Sutiman Bambang Soemitro (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Purpose: The aim of this study were to determine the association of increasing of FasL with increasing proliferation of retinoblastoma cells. Materials and Methods: The protein expression was analyzed in 30 retinoblastoma samples from paraffin block using immunohistochemical method for evaluation of FasL, CDK4, and Ki-67 expression. Results: Among 30 retinoblastoma samples, FasL expression majority was negative in 33.3 % (10 samples) and strong in 36,8 % (11 samples). CDK4 majority 53,3% was weak expression and Ki-67 was high expression also in 53,3% (16 samples). The expression of FasL was significantly related to CDK4 (r: 0.363; p: 0.048). The CDK4 was also significantly related to Ki-67 expression (r: 0.601; p: 0.000). Conclusion: The increasing of FasL on the mechanism Fas counterattack induces proliferation of retinoblastoma cells. [Cukurova Med J 2014; 39(4.000): 788-794]